MASSACHUSETTS EXCISE TAX INITIATIVE TAX CAMPAIGN - STEVENS,AJ (Tufts Archival Research Center, 2007)
Tobacco Institute breakdown of cost sharing among tobacco companies for the Massachusetts excise tax intiative tax campaign.